EFEKTIVITAS RELAKSASI OTOT PROGRESIF TERHADAP PENURUNAN INTENSITAS NYERI DISMENORE PADA REMAJA PUTRI - Chandra Sulistyorini (Jurnal Medika : Karya Ilmiah Kesehatan, 2019)
Background: Dysmenorrhea is a painful condition at the abdominal area, cramps and back pain which can disturb daily activities. The prevention done by female teenagers to avoid dysmenorrhea were to ignore it, hold their stomach, take some herbal drinks, lie down and watch television. Some even skip the classes at school and go home during school days, in which 20 % of them go to the school medical room to take a rest when experiencing dysmenorrhea. Aim: To identify the effectiveness of progressive muscle relaxation on reducing dysmenorrhea pain intensity of female teenagers. Method: This research used the pre-post-test quasi experimental without control design. The sampling technique was accidental sampling with 35 respondents, gathered from April to May 2018. The data were analysed by using Wilcoxon test while the pain intensity was measured by using numerical rating scale and progressive muscle relaxation SOP. Findings: The pain intensity value before the intervention was 5.00 and the value after the intervention was 3.00. The statistical analysis by using Wilcoxon Test showed that the sig value (2-tailed) was 0.000, which was < 0.05. It means that there was a significant difference between the pre and post-test results of the pain intensity. Conclusion: Progressive muscle relaxation had an effective on reducing dysmenorrhea pain intensity. Therefore, it is suggested that female teenagers be able to do a progressive muscle relaxation twice a day before and during the menstruation period in order to reduce the pain intensity and as an alternative for the treatment and prevention of pre-menstrual pain.